The safety of meperidine prescribing in older adults: A longitudinal population-based study. Issue 1 (December 2016) - Friesen, Kevin; Falk, Jamie; Bugden, Shawn
Abstract Background Meperidine (pethidine) is an opioid analgesic that offers little advantage relative to other opioids and several disadvantages including limited potency, short duration of action, and the production of a neurotoxic metabolite (normeperidine) with a long half-life. Older adults are more sensitive to meperidine's side effects and may have diminished renal function which leads to the accumulation of normeperidine. The Institute for Safe Medication Practices has suggested avoiding meperidine in older adults, limiting its dose (≤600 mg/day) and duration of use (≤48 h). The objective of this study was to determine the level of meperidine use in older adults and assess the dosage and duration of meperidine with reference to these safety recommendations. Methods A longitudinal study using administrative healthcare data was conducted to examine meperidine utilization and levels of high dose and extended duration prescribing among persons ≥65 years of age between April 1, 2001, and March 31, 2014 in Manitoba, Canada. The number of meperidine prescriptions, users, duration of treatment, defined daily doses (DDD) dispensed and number of prescribers were determined over the study period. Results In the Manitoba older adult population there was a marked decline in meperidine users and prescriptions from 2001 to 2014. There was an average use of 26.4 (95 % CI 24.0–28.8) DDDs of meperidine per user per year. While only 3.7 % of the prescriptions exceeded the 600 mg maximum daily dose, 96.7 % of prescriptions exceeded the recommended 2 days of therapy. For the remaining users of meperidine, the amount of meperidine used per person rose from 18.98 to 56.14 DDDs/user/year over the study period. The number of prescribers of meperidine declined throughout the study, but low DDD prescribers declined more quickly than high DDD prescribers. Conclusions While meperidine use has declined, the remaining use appears to be decreasing in safety, with more meperidine prescribed per user. This seems to be driven by the continued prescribing by a small number of high DDD prescribers. Targeted educational initiatives directed at this small group of prescribers may be helpful. Alternatively removing meperidine from medication insurance schemes may provide additional incentive to avoid meperidine in older adults.